1996
DOI: 10.1103/physrevlett.76.3176
|View full text |Cite
|
Sign up to set email alerts
|

Insulator-Metal Transition in the One- and Two-Dimensional Hubbard Models

Abstract: We use Quantum Monte Carlo methods to determine T = 0 Green functions, G( r, ω), on lattices up to 16 × 16 for the 2D Hubbard model at U/t = 4. is approached from the insulating phase. ξ l may be interpreted as the localization length involved in transferring a particle over a distance r from the electronic system to the heat bath lying at energy µ within the charge gap. Under the assumption of hyperscaling, the above quantities are expected to satisfy the scaling relations:where The Hubbard model we consider … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 17 publications
6
44
0
Order By: Relevance
“…This large dynamical exponent z = 4 is indeed supported in a number of independent numerical calculations for the filling-control transition of the Hubbard model in two dimensions at T = 0, 23,24,36,[38][39][40][41] which suggests that T ch is zero or very small in this case.…”
Section: Phenomenological Constructionmentioning
confidence: 61%
“…This large dynamical exponent z = 4 is indeed supported in a number of independent numerical calculations for the filling-control transition of the Hubbard model in two dimensions at T = 0, 23,24,36,[38][39][40][41] which suggests that T ch is zero or very small in this case.…”
Section: Phenomenological Constructionmentioning
confidence: 61%
“…The diverging behavior of was reported by the quantum Monte Carlo (QMC) simulations 7,14) performed on the same model with larger system sizes not yet treated by exact-diagonalization studies. The QMC calculation 15) also demonstrated that the localization length suggests the divergence l / j À c j À with ¼ 1=4 as the chemical potential approaches the charge gap c from the insulating side. The scaling theory indicates z ¼ 1, which also leads to the exponent z ¼ 4.…”
Section: -4)mentioning
confidence: 99%
“…(18). For the two-dimensional system, d = 2, the dynamical exponent z = 4 was identified by numerical calculations, 23,24 and then the same critical behavior for χ c as the d = 1 case appears. For the three-dimensional system, in the case of z = 4, the charge compressibility has the form of χ c ∼ (µ c − µ) −1/4 by eq.…”
mentioning
confidence: 99%